CONTROLLED RELEASE OF GABAPENTIN THROUGH RETICULATED CHITOSAN AND HYDROXYETHYL CELLULOSE HYDROGEL MATRIX TABLETS - Narasimha S. Managoli (Indonesian Journal of Pharmacy, 2014)
The aim of the present work was to prepare hydrogel matrix tablets using crosslinked chitosan and hydroxyethyl cellulose (HEC) for controlled release of gabapentin. The chitosan was crosslinked with acetaldehyde and used for the preparation of hydrogel matrix tablets along with hydroxylethyl cellulose by wet granulation method. The samples were characterized by FTIR, DSC, TGA, XRD, SEM and evaluated drug content, swelling pattern and drug release. The matrix tablets were capable of releasing the drug for 24h depending upon the formulation variables. It was observed that as the concentration of HEC increased in the tablets, the drug release was also increased. On the other hand, as the crosslinking of chitosan was increased, the drug release was decreased. Drug release mechanism followed non-Fickian transport. This study demonstrated that the blend hydrogel matrix tablets of crosslinked chitosan and HEC could be a versatile drug delivery system for controlled release of gabapentin.